COMUNICAÇÃO & ASTRONOMIA: UMA UNIÃO VIRTUAL Estudos para uma teoria de comunicação organizacional on-line a partir do caso Rede de Astronomia Observacional REA/Brasil - Trevisan, Nanci Maziero (2005)
The thesis "Communication & Astronomy, a virtual union" approaches the universe of the virtual communication, of the virtual organizations, of virtual science. A new and emotive universe where the asynchronous relation space-time is the common factor to all the involved social actors. The universe of the virtual one, of the related tools of communication to the new technologies, of ciberespace, of the concrete existence of an incorporeal organization. These new elements open horizons for the knowledge and understanding of the communication processes human being and organizacional in the age of the informacional revolution, providing the chance to establish a theory of organizacional communication on line. The bibliographical research was supported in three theorical bases of reference: the computer mediated communication, virtual communication and organizacional communication, these bases had the support of a case study that constituted the corpus of the study. We could then understand how the communication in a virtual organization occurs, its processes, crucial tools and points that can be summarized in the necessary motivacional factor to the stimulation for a coo perative virtual interaction, necessity of construction and maintenance of strong institucional image that delimits the organization in ciberespaço and clear definition of the codes of behavior of the virtual organization.(AU)